Mental diseases and criminal offences committed by persons placed at the Forensic Department of the Penitentiary in Zenica, Federation of Bosnia and Herzegovina - Edin Bjelošević; Adisa Krehmić; Halima Hadžikapetanović; Sanel Čoralić; Sonja Bjelošević (Medicinski glasnik, 2017)
Aim: To investigate an impact of various biological, psychological and social factors on perpetration of criminal offences by persons with mental disorders and to examine legal requirements for placement of persons with mental disorders, who committed criminal offences. Methods: This retrospective, descriptive study based on the analysis of data collected from records of the Zenica Penitentiary, Forensic Department (age, qualifications, employment status, marital status, mental disorders, information related to earlier treatments, type of committed criminal offense, duration of the security measure of mandatory psychiatric treatment and custody) included 154 examinees. Results: The study included 154 male examinees. An average age of the examinees was 34 years. An average duration spent at the Forensic Department was 3 years, murder was committed by 68 (44.15%) examinees, and 34 (22.07%) examinees committed attempted murder. Eighty-five (55. 19 %) examinees suffered from schizophrenia, 30 (19.48%) had delusional disorder, and 19 (12.33%) had mental retardation. Conclusion: The highest number of committed crimes was in correlation with schizophrenia, (the highest number of examinees suffered from schizophrenia). It is necessary to work on the establishment of a forensic hospital in the territory of the Federation of Bosnia and Herzegovina in order to create good conditions for rehabilitation of patients with mental disorders who committed criminal offences.
Keywords: schizophrenia; accountability; murder